2016
DOI: 10.7554/elife.19089
|View full text |Cite
|
Sign up to set email alerts
|

Decoding gripping force based on local field potentials recorded from subthalamic nucleus in humans

Abstract: The basal ganglia are known to be involved in the planning, execution and control of gripping force and movement vigour. Here we aim to define the nature of the basal ganglia control signal for force and to decode gripping force based on local field potential (LFP) activities recorded from the subthalamic nucleus (STN) in patients with deep brain stimulation (DBS) electrodes. We found that STN LFP activities in the gamma (55–90 Hz) and beta (13–30m Hz) bands were most informative about gripping force, and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 44 publications
5
62
1
Order By: Relevance
“…Published studies on decoding the force of hand grasp generally assumed a linear relation between brain oscillatory activity, such as beta and gamma-band power of ECoG or LFP, and grasp force (Chen et al, 2014;Flint et al, 2014;Milekovic et al, 2015;Tan et al, 2016). However, in this study, we show that the dynamics of LFB-ERD and HFB-ERS were more congruent with the first time-derivative of force rather than force itself.…”
Section: Possible Challenges In Ecog Decoding For Sustained Hand Graspcontrasting
confidence: 71%
“…Published studies on decoding the force of hand grasp generally assumed a linear relation between brain oscillatory activity, such as beta and gamma-band power of ECoG or LFP, and grasp force (Chen et al, 2014;Flint et al, 2014;Milekovic et al, 2015;Tan et al, 2016). However, in this study, we show that the dynamics of LFB-ERD and HFB-ERS were more congruent with the first time-derivative of force rather than force itself.…”
Section: Possible Challenges In Ecog Decoding For Sustained Hand Graspcontrasting
confidence: 71%
“…Motor vigor describes the gain of the parameters for a purposive action, that is, speed or amplitude ( Turner and Desmurget, 2010 ; Panigrahi et al, 2015 ; Tan et al, 2015 ) and increasing evidence from animal models suggests that the encoding of motor vigor, with special emphasis on movement speed, is strongly dopamine dependent ( Panigrahi et al, 2015 ; Yttri and Dudman, 2016 ). Several studies have shown in patients with Parkinson’s disease ON medication that subthalamic gamma synchrony scales with kinematic parameters albeit primarily focusing on force instead of velocity modulated movements ( Anzak et al, 2012 ; Joundi et al, 2012 ; Tan et al, 2013 ; Tan et al, 2016 ; Fischer et al, 2017 ). Given that patients with Parkinson’s disease OFF medication display increasingly bradykinetic and decrementing movements as signs of reduced motor vigor, the question arises whether dopamine affects the scaling capacity within the gamma frequency range.…”
Section: Discussionmentioning
confidence: 99%
“…Here, beta oscillations may carry information that goes beyond a simple preparation signal. Recently, it has been reported that movement and force are encoded in beta oscillations (Tan et al, ). In fact, previous studies suggested that beta oscillations can be content specific, enabling them to carry information about currently processed tasks.…”
Section: Discussionmentioning
confidence: 99%